EKSISTENSI PENDIDIKAN ANTI KORUPSI SEBAGAI BENTUK PENDIDIKAN KARAKTER DI UNIVERSITAS DALAM MELAHIRKAN GENERASI PENERUS BANGSA YANG ANTI KORUPSI - Made Kharisma Putri (Universitas Pendidikan Ganesha, 2023)
Anit-Corruption education was born as a study at a higher level, which is part of character education for students. This is to produce students who are honest, intelligent, have good character and have intergrity as the next generation of the nation who will guide Indonesia towards goodness. Thins is also an effort to prevent and reduce the eradication of corruption in Indonesia because in this corruption case Indonesia is already ranked fifth out of eight ASEAN countries. One of the manifestations of anti-corruption education is by implementing anti-corruption values and principles to inhibit the influence of interl abd external factor. The Purpose if this research is ti develop and students so that they are not affected by acts of corruption by intilling themselves with anti-corruption values and principles. And the method applied in wrting this article is descrivtive qualitative coupled with the application of the literature study method.